2022
DOI: 10.35542/osf.io/h5kc7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding English as a Foreign Language Students’ Idea Generation Strategies for Creative Writing With Natural Language Generation Tools

Abstract: Text generation is a function of artificial intelligence (AI) natural language processing. It can become an integral part of a human’s creative writing process. Importantly, a youths can learn to apply text generation in mainstream education and become better prepared for an AI-enhanced creative writing job and other writing endeavors. To explores how a student applies text generation to creative writing, we designed and implemented a 1st Human-AI Creative Writing Contest in a Hong Kong secondary school. In th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This means that students use these tools more when they are in need of enhancing their overall writing, regardless of their perceptions. In the same way, this finding relates to studies conducted by Dong (2023), Hwang and Nurtantyana (2022), Yang (2007), Woo et al (2023). These studies on AI tools in education have demonstrated significant potential for improving writing proficiency among EFL learners.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This means that students use these tools more when they are in need of enhancing their overall writing, regardless of their perceptions. In the same way, this finding relates to studies conducted by Dong (2023), Hwang and Nurtantyana (2022), Yang (2007), Woo et al (2023). These studies on AI tools in education have demonstrated significant potential for improving writing proficiency among EFL learners.…”
Section: Discussionsupporting
confidence: 75%
“…In addition to these benefits, Ali (2020) argued that the utilization of AI in education facilitates a shift towards a student-centered approach, resulting in the empowerment of learners. The utilization of AI tools in education has shown great potential for enhancing writing proficiency among English as EFL learners (Dong, 2023;Hwang and Nurtantyana, 2022;Yang, 2007;Woo et al, 2023). Godwin-Jones (2022) maintained that AI-powered writing tools can significantly enhance the quality of learners' written compositions.…”
Section: Introductionmentioning
confidence: 99%
“…ChatGPT's rapid feedback and interactive learning experiences enriched the students' educational journey by boosting motivation, engagement, and better information retention (Mogavi et al., 2023; Murgia et al., 2023). Furthermore, the introduction of ChatGPT into education has shown the potential to reduce language barriers and enhance student accessibility (Lou, 2023;Othman, 2023; Woo et al., 2023). These findings demonstrate ChatGPT's revolutionary potential as an innovative and helpful tool to enhance and enrich the learning process in K‐12 educational environments, as well as being relevant steps in co‐design for learning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ChatGPT can be used to prepare lessons by providing valuable insights, resources, and teaching strategies, thereby making the process of lesson planning more efficient and effective (Bekeš & Galzina, 2023; Küchemann et al., 2023; Lou, 2023). ChatGPT can assist teachers in many ways as instructional assistants, such as by addressing common inquiries, facilitating discussions, and providing students with immediate feedback (Alneyadi & Wardat, 2023; Dao, Le, Phan, et al., 2023; Murgia et al., 2023; Woo et al., 2023). Another significant implication for educators is the preparation of assignments and tests (Alneyadi & Wardat, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation